Penerapan Media Pembelajaran Roda Pintar untuk Meningkatkan Kemampuan Membaca Permulaan Peserta Didik di Sekolah Dasar - Janah, Ruziyatun; Rosyidatul Kholidah, Dwi (IBTIDA’, 2025)
This study was conducted to examine the effectiveness of the Smart Wheel learning media in improving the reading skills of first-grade students at MI Salafiyah Banin Banat Siman. The research employed an experimental method using a One Group Pretest-Posttest Design. The implementation took place over four meetings in June 2025, involving 29 students as the research subjects. The first meeting was dedicated to administering the pretest, while the following three meetings focused on applying the Smart Wheel media through activities in which students spun the wheel containing letters, syllables, and simple words to be read alternately. In the final meeting, a posttest was given to assess the development of students’ reading skills.Data collection techniques included observation of students’ learning activities, initial reading skill tests, and relevant documentation. The instruments used consisted of an observation sheet for reading performance and an initial reading test. The collected data were analyzed quantitatively by comparing the pretest and posttest scores to determine the improvement in students’ reading ability after the use of the Smart Wheel media.The findings showed that students demonstrated a very high level of engagement during the learning process, with an average percentage of 90.23%. The average pretest score was 43.20%, classified as the moderate category, whereas the average posttest score increased to 67.60%, which is categorized as high. Based on the Paired Sample T-Test analysis, the obtained t-value was -24.642 with a significance level of 0.000 (< 0.05). Therefore, it can be concluded that the Smart Wheel media has a significant effect on enhancing students’ reading ability.In summary, the Smart Wheel media is proven to be effective in developing early reading skills, particularly in letter recognition, pronouncing syllables, and reading simple words.